Identity Boundaries and Place Construction in Tom Cho’s I, Robot, and Pinocchio - Kušnír, Jaroslav; Pavlikova, Martina (Journal of Education Culture and Society, 2024)
Thesis. Using the example of two literary works, the contribution reflects the influence of media and technology on the formation of an individual's personality and on his or her value orientations. The starting point is a comparison of the works I Robot and Pinocchio with a focus on the question of individual identity. In the mentioned works, we mainly observe the relationship between the attempt to escape from technology and, at the same time, the inability to break free from dependence on technology.Concept. Based on a comparison of the motives in the behaviour of the heroes of the studied works, we analyse the key aspects that lead a young person to become aware of the risks associated with the use of technology. We focus on those moments in which a person faces moral dilemmas when using technology. We pay special attention to the penetration of technology into the essence of the human person and the creation of a certain hybrid form of a person who is also a machine.Results and conclusion. Both the personal and cultural identity of the protagonist is linked to the creation of believable "lies" represented by media, pop culture and technology, believable from the point of view of this young protagonist and his girlfriend, and thus their personal and cultural identities become empty, fluid and merging with the image that these characters create about themselves, their identity and the reality represented by stories, fantasies, TV shows and lies that they believe more than the reality outside them, that is, the cultural identities of most of the protagonists.